Corporate governance and detrimental related party transactions: Evidence from Malaysia. Issue 2 (7th May 2019) - Fooladi, Masood; Farhadi, Maryam
Abstract : Purpose: Prior studies suggest that most expropriation of firm's resources is conducted through related party transactions (RPTs). Based on the conflict of interest view, related parties opportunistically use their authorities to expropriate firms' resources for their own benefits via RPTs subsequently increasing agency costs and reduce firm value. One important monitoring system suggested by agency theory to reduce the agency problem is corporate governance (CG). CG monitors firm's performance to align the interests of those who control and those who own the residual claims in a firm. The purpose of this paper is to investigate the moderating effect of CG characteristics on the relationship between RPTs and firm value. Design/methodology/approach: In order to clarify the distinct effect of RPTs, this study categorises RPTs into two groups including beneficial and detrimental RPTs (DRPTs). Applying "proportionate stratified random sampling", this study covers a panel of 271 firms listed on Bursa Malaysia over the period of 2009–2011, using a moderated multiple regression model. Findings: This study documents that firm value is positively associated with beneficial RPTs (BRPTs) and negatively related to detrimental RPTs (DRPTs). In addition, results show that divergence can intensify the negative relationship between DRPTs and firm value. Findings support the necessity for more scrutiny by regulators, policy makers and standard setters to monitor the conflict of interests in RPTs and restrain the power of related parties to protect the firm's wealth by introducing stricter regulations for RPTs and improve CG practices especially to monitor RPTs in order to limit the opportunistic behaviour of related parties. Research limitations/implications: Research implications have been presented in Section 10. It has also been summarised in practical implications and social implications sections. Practical implications: The findings of this study indicate that investors, creditors and policy makers should not consider all RPTs as harmful transactions and it seems necessary to categorise RPTs into different groups including transactions which are detrimental and transactions which are beneficial to the firm. Social implications: The findings of this study support the necessity for more scrutiny by regulators, policy makers and standard setters to monitor the conflict of interests in RPTs. They should restrain the power of related parties to protect the firm's wealth by introducing stricter regulations for RPTs and improving CG practices especially to monitor RPTs in order to limit the opportunistic behaviour of related parties. Originality/value: This study contributes to the RPTs literature by showing that the effect of RPTs on firm value depends on the types of RPTs, and market participants allocate different values to different types of RPTs. Therefore, to fill the gap and clarify the distinct effect of RPTs, this study categorizes RPTs into two groups including beneficial and detrimental RPTs.